Birth Trauma in Maternal and Neonatal Emergency Management for Paramedics, Epidemiologists, Trauma Specialists, and Nursing Teams-An Updated Review - Aljouhani, Nader Abdulhadi; Alshahrani, Hassn Dairem; Aladhyani, Mohammed Muqhim; Alotaibi, Abdulaziz Rubayy; Alotaibi, Saleh Eid; Hadi Alqahtani, Asma Saad; Ali Alzahrani, Raoud Ahmed; Fatini Oraibi, Saleh Maeeish; Alotaibi, Fuad Khalaf; Al-Areej, Ibrahim Mohammed (International Journal of Aquatic Research and Environmental Studies, 2025)
Background: Birth trauma is a multifactorial condition involving physical and psychological injuries to the mother and neonate during labor and delivery. It remains a significant contributor to short- and long-term morbidity worldwide. Aim: To provide a comprehensive synthesis of maternal and neonatal birth trauma, including risk factors, clinical manifestations, complications, and preventive strategies across multidisciplinary healthcare settings. Methods: A narrative synthesis approach was used to review evidence on maternal physical injuries, neonatal trauma, intracranial and extracranial hemorrhages, brachial plexus injuries, and psychological sequelae. Emphasis was placed on epidemiological trends, clinical classification, diagnostic approaches, and interprofessional management strategies. Results: Findings demonstrate that maternal injuries are primarily perineal lacerations associated with pelvic floor dysfunction, urinary and fecal incontinence, and sexual dysfunction. Neonatal injuries include scalp lesions, skull fractures, intracranial hemorrhages, and nerve injuries such as brachial plexus palsies. Psychological trauma affects a substantial proportion of birthing individuals, with PTSD symptoms reported in up to 12.3% and traumatic perception in up to 50%. Risk factors include fetal size, malpresentation, operative delivery, obstetric complications, and psychosocial vulnerability. Preventive strategies require coordinated antenatal risk assessment, skilled intrapartum management, and postpartum surveillance. Conclusion: Birth trauma remains a preventable yet significant clinical challenge requiring integrated obstetric, emergency, neonatal, nursing, and public health approaches to optimize outcomes.